Effects of coordination-based training on preschool children’s physical fitness, motor competence and inhibition control - Beyza Başarır; Umut Canlı; Ali Mert Şendil; Cristina Ioana Alexe; Răzvan Andrei Tomozei; Dan Iulian Alexe; Lucian Ovidiu Burchel (BMC Pediatrics)
Abstract Aim This study aimed to investigate the effects of a coordination-based training program on physical fitness, motor competence, and inhibition control in preschool children. Method Fifty-one preschool children aged 5 to 6 years (M = 6.03, SD = 0.30), were randomly assigned to either an exercise group (EG; n = 26), which received a coordination-based training program, or a control group (CG; n = 25), which continued their routine activities. All participants were recruited from a preschool. Physical fitness (PF) was assessed through agility, static and dynamic balance, and vertical jump tests. Motor competence (MC) was measured using the Körperkoordinationstest für Kinder 3+ (KTK3+), and inhibition control (IC) was evaluated via the Go/No-Go test. Result The group-time interaction showed that the exercise group’s score increase was significantly higher than that of the CG in vertical jumping (F(1−49) = 14.569, p < 0.001, η p 2   = 0.229) and KTK Balancing Backwards (F(1−49) = 14.051, p < 0.001, η p 2   = 0.223) variables. Also, CG’s score increase was significantly higher than that of the EG in KTK Moving Sideways (F(1−49) = 9.984, p < 0.01, η p 2   = 0.169). However, statistically significant differences were not found in the comparison of group x time interaction in all other variables (p > 0.05). Conclusion The coordination-based training provided to the exercise group led to significant improvements in vertical jump performance (an indicator of lower extremity strength) and KTK Balancing Backwards scores (an indicator of dynamic balance) compared to the control group. These findings suggest that coordination-based training can enhance lower extremity strength and dynamic balance in preschool children.